Association of choroid plexus volume with white matter microstructure, glymphatic function, and peripheral systemic inflammation in Alzheimer’s disease - Huwei Xia; Yijia Feng; Han Zhu; Danlu Yang; Chaoqun Wang; Zhipeng Wang; Hanyuan Zhang; Wenhao Pan; Yifan Zhao; for the Alzheimer’s Disease Neuroimaging Initiative; Weihong Song; Yili Wu (Translational Psychiatry)
Abstract There has been growing attention to the role of choroid plexus (CP) in neurodegenerative diseases. However, its relationship with various pathophysiological changes in Alzheimer’s Disease (AD) remains unclear. The purpose of this study is to investigate the relationship between CP volume (CPV) and white matter microstructure, cognitive function, glymphatic function, and peripheral systemic inflammation in AD. A total of 1351 participants with cognitive impairment who had available 3 T MRI scans were included from ADNI. CPV was automatically segmented using Gaussian Mixture Model (GMM). The Mini-Mental State Examination (MMSE) was employed to assess cognitive function. PSMD and DTI-ALPS based on DTI sequence were used to reflect white matter microstructure and glymphatic system. Peripheral systemic inflammation was represented by the neutrophil-lymphocyte ratio (NLR). Group comparisons and correlations were adjusted for age, sex, education and APOE4 carrier status. Participants with AD exhibited larger CPV (p < 0.001), higher PSMD (p < 0.001) and NLR (p = 0.035), and lower DTI-ALPS (p < 0.001) compared to those with subjective cognitive decline (SCD). CP enlargement was independently associated with higher PSMD (β = 0.223, p < 0.001) and worse cognitive function both cross-sectionally (β = −0.212, p < 0.001) and longitudinally (β = −0.214, p < 0.001). Furthermore, PSMD partially mediates the impact of CP enlargement on the severity and progression of cognitive function. Partial correlation analysis revealed that CP enlargement was associated with higher NLR (r = 0.101, p = 0.001) and lower DTI-ALPS (r = −0.241, p < 0.001). These findings suggest that CPV may reflect underlying pathophysiological processes in AD and serve as a biomarker for white matter damage and cognitive impairment progression.